Penggunaan Digital Marketing di PT. Bank Syariah Indonesia dengan Pendekatan Search Engine Optimization (SEO) - Annadafah; Muayyad, Ubaidullah (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2022)
Promotions using digital marketing are expected to reach more customers. The increasingly massive use of digital marketing aims to measure the increase in the consumer movement from various digital platforms. The tool to measure digital marketing performance in this research is by using Search Engine Optimization (SEO). It is an approach used by companies to increase position or sales in natural or organic results listings to search for selected keywords or phrases. This research is exploratory qualitative research with secondary data sources through the digital marketing network of PT. Bank Syariah Indonesia. The data collection technique is documentation, while the data analysis technique uses the Miles and Huberman model which uses the stages: a) data reduction; b) data presentation; and c) drawing conclusions or verification. The findings of this study are PT. Bank Syariah Indonesia carries out digital promotions with several concepts such as digital devices, digital platforms, digital media, digital data, and digital technology. Digital marketing conducted by PT. Bank Syariah Indonesia through the search engine optimization (SEO) approach is said to be successful based on observations over the last three months, which shows that there has been a significant increase in marketing. This indicates that digital marketing campaigns are getting a good response from internet user customers. Thus, PT. Bank Syariah Indonesia through digital marketing can meet customer expectations and satisfaction.